Differences in gene expression may contribute to the racial differences in the risk of MASLD - Ivan P. Gorlov; Olga Y. Gorlova; Aaron P. Thrift (PLoS ONE, 2026)
Metabolic dysfunction-associated steatotic liver disease (MASLD), formerly known as non-alcoholic fatty liver disease (NAFLD), exhibits marked racial disparities in incidence, progression, and clinical outcomes. While diet, lifestyle, and socioeconomic factors have been shown to influence these disparities, biological mechanisms underlying racial differences in MASLD risk remain poorly understood. We hypothesized that race-associated variation in hepatic gene expression may contribute to differential susceptibility and progression of MASLD. To test this hypothesis, we analyzed publicly available gene expression data from liver biopsies obtained from over 300 Black and White individuals undergoing bariatric surgery. Gene expression profiles were compared across four histological stages: normal liver, MASLD, metabolic dysfunction-associated steatohepatitis (MASH) without fibrosis, and MASH with fibrosis. We identified more than 200 genes that were significantly differentially expressed between Black and White individuals. Genes associated with MASLD progression were significantly enriched among race-specific genes, supporting the hypothesis that racial differences in hepatic gene expression contribute to disease risk and progression. Using histologically normal liver as a reference, we identified race-specific candidate genes potentially driving MASLD progression. These included UCN3 and PRSS3 in Black individuals, and MMP15, LAMB2, LEPR, ELOVL2, CD48, COL5A2, and ICAM1 in White individuals. Notably, divergence in gene expression profiles between racial groups became more pronounced with advancing disease stages, suggesting that race may play an increasingly important role in later phases of MASLD progression. Our findings indicate that differential modulation of hepatic gene expression represents a potential biological mechanism contributing to racial disparities in MASLD. These results highlight the importance of considering race-specific molecular signatures in understanding MASLD pathogenesis and in developing targeted prevention and therapeutic strategies.